Pendekatan Yuridis dan Normatif tentang Sanksi Bagi Hakim Pelanggar - Hardani H; Asni A; Halim Talli (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The integrity of the justice system relies heavily on judges' adherence to the Code of Ethics and Code of Conduct for Judges (KEPPH). This study aims to legally and normatively analyze the grounds for imposing sanctions on judges who violate the code of ethics, viewed from the perspectives of moral philosophy and procedural law. This research employs a normative-juridical method with a conceptual approach. The findings indicate that sanctions for judges are based not merely on violations of positive law, but on breaches of fundamental professional ethics principles comprising honesty, moral independence, and both vertical and horizontal accountability. Administrative negligence in the case file examination process that results in substantive injustice constitutes a fundamental basis for applying ethical sanctions. Judicial professionalism demands the unification of technical juridical competence with autonomous moral integrity.